The Influence Of Parental Career-Related Behavior On Career Anxiety And Career Decision Making - Martiani, Heni Trisna; Purwanto, Edy; Mugiarso, Heru (Jurnal Bimbingan Konseling, 2023)
Making career decisions is crucial for students to determine the education or job that aligns with their interests, talents, or opportunities in line with their vocational identity. This study aimed to analyze the impact of parental career-related behavior on three aspects: support, interference, and lack of engagement on career anxiety and career decision-making. It was a quantitativeresearch with a correlational research design and involved 297 twelfth graders at vocational high school (SMK) as the samples. Following the students’ data analysis there found that parental career-related behavior, regarding support and lack of engagement significantly influenced career anxiety and decision-making. In contrast, the interference aspect only significantly affected career anxiety, but not career decision-making. Furthermore, career anxiety significantly affected career decision-making. Lasltly, this study provides insight into parental involvement (parental career-related behavior) in students' career development. High career anxiety should be reduced to enhance student's ability to make career decisions.